2009
DOI: 10.1007/s10763-009-9186-7
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Effectiveness of Inquiry-Based Instruction on Students With Different Prior Knowledge and Reading Abilities

Abstract: This study examined the differential impacts of an inquiry-based instruction on conceptual changes across levels of prior knowledge and reading ability. The instrument emphasized four simultaneously important components: conceptual knowledge, reading ability, attitude toward science, and learning environment. Although the learning patterns and effect size analyses indicated that students from all subgroups demonstrated substantial gains on weather concepts, students from the low prior conceptual knowledge grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
12
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 27 publications
(32 reference statements)
3
12
0
Order By: Relevance
“…It is in line with the result of previous researches that also investigated the inquiry based laboratory activity, such as the result of a research conducted by Wolf and Fraser (2007) which showed that inquiry based laboratory activity was effective to improve students' achievement [10], research conducted by Wang (2008) also showed the same result, it showed inquiry based laboratory activity gave a statistically significant effect toward the students' conceptual changes across levels of prior knowledge and reading ability [15].…”
Section: Conceptual Understandingsupporting
confidence: 87%
“…It is in line with the result of previous researches that also investigated the inquiry based laboratory activity, such as the result of a research conducted by Wolf and Fraser (2007) which showed that inquiry based laboratory activity was effective to improve students' achievement [10], research conducted by Wang (2008) also showed the same result, it showed inquiry based laboratory activity gave a statistically significant effect toward the students' conceptual changes across levels of prior knowledge and reading ability [15].…”
Section: Conceptual Understandingsupporting
confidence: 87%
“…Wenger (1998) refers to this as 'legitimate peripheral participation' and explains that on entry to each new community, learners become legitimate peripheral participants who have some experience of educational practices but who, at this periphery stage, do not know if the practices that had previously guaranteed success, and that had been valued by the members of the old community, are equally valid and valued in the new community. This links in well with what we present in the literature review about the role of students' efficacy beliefs in achieving success in learning science (Wang, Wang, Tai and Chen 2010). Thus, it seems that depending on whether or not the participants are able to transfer the practices between the communities, they might or might not become full participants (O'Donnell and Tobbell 2007).…”
supporting
confidence: 75%
“…We therefore explore the role of the students' English language proficiency and science background knowledge in this study, trying to understand, through the lens of CoP, how our students negotiate their identities when crossing boundaries between the communities of their schools and the university at which they currently study. Wang et al (2010) claim that prior science knowledge and L2 proficiency are two very important traits that play a major role in acquiring the scientific material to be studied. Their findings suggest that learning science in a new setting is a complex process in which "experiences and information are processed through the lens of a learner's comprehension of science language, epistemological beliefs, efficacy beliefs and metacognitive skills" (ibid.…”
Section: Subject Background Knowledge and Foreign Language Proficiencymentioning
confidence: 99%
See 1 more Smart Citation
“…What has not yet been addressed, however, and should be further explored in future research, is whether prior achievement or prior knowledge of ecology modifies the relationships that were presented in this study. Some scholars have shown that prior knowledge or achievement can affect how students interact with an inquiry-oriented curriculum (e.g., Chen & Wu, 2012;Olympiou, Zacharias, & deJong, 2013;Wang et al, 2010).…”
Section: Limitations and Delimitationsmentioning
confidence: 99%